Circulating soluble ICAM-1 and subclinical atherosclerosis: The Coronary Artery Risk Development in Young Adults (CARDIA) Study - Gross, Myron D. (2011)
BACKGROUND: Soluble intercellular adhesion molecule-1 (sICAM-1) is associated with endothelial dysfunction and clinical cardiovascular disease. We investigated the relationship of subclinical atherosclerosis with sICAM-1 concentration. METHODS: sICAM-1 concentration was assayed at year 15 of the Coronary Artery Risk Development in Young Adults (CARDIA) Study (black and white men and women, average age 40 years). We assessed progression of coronary artery calcification through year 20 (CAC, n=2378), and both carotid artery stenosis (n=2432) and intima media thickness at year 20 (IMT, n = 2240). RESULTS: Median sICAM-1 was 145.9 ng/ml. Among a subgroup with advanced atherosclerotic plaque (either CAC or stenosis), IMT was 0.010 (95% confidence interval (CI) 0.003–0.017 mm) higher per standard deviation of sICAM-1 (44 ng/ml) in a model adjusted for age, race, sex, clinic, smoking, exercise, body size, education, blood pressure, antihypertensive medication, plasma lipids, and cholesterol lowering medication. With the same adjustment, the odds ratios (OR) for the presence of year 20 carotid artery stenosis per SD of sICAM-1 was 1.12 (CI 1.01–1.25, p<0.04), while for occurrence of CAC progression the OR was 1.16 (CI 1.04–1.31, p<0.01). The associations with CAC and carotid stenosis were strongest in the top 20(th) of the sICAM-1 distribution. CONCLUSION: sICAM-1 concentration may be an early biomarker that indicates changes in the artery wall that accompany atherosclerosis, as well as the presence of advanced plaque in the coronary and carotid arteries. This finding holds in people with low total burden of atherosclerosis, decades prior to the development of clinical CVD.